Anti-myelin oligodendrocyte glycoprotein – antibody presenting as tumefactive demyelination and hemiparesis in a pediatric patient - N, Meghana; G, Architha; A, Jyotsna; Prashanth, S; A, Ramu; Savitha, MR (Indian Journal of Child Health, 2024)
Anti-myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease is an immune-mediated central nervous system demyelinating disorder with a variety of phenotypic presentations such as acute disseminated encephalomyelitis, optic neuritis, and transverse myelitis but rarely presents as tumefactive lesion, particularly in children. We present a case of an adolescent girl with an anti MOG antibody-related disorder that manifested as a tumefactive lesion.